PERSENTASE PENURUNAN KADAR β–KAROTEN PADA PENGOLAHAN MINYAK GORENG CURAH DAN KEMASAN - Dwimaryam Suciati; Chessia Nodifa Putri (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
β-carotenes is the most active form of provitamin A. β-carotenes has similar properties to vitamin A, which are sensitive to oxygen, light, and heat. Oxidation of β-carotenes is a major cause of reducing levels of β-carotenes in food. The samples used in this study are CPO (Crude Palm Oil), BPO (Bleached Palm Oil), RBDPO (Refined Bleached Deodorized Palm Oil), and RBD Olein (Refined Bleached Deodorized Olein) in the processing of CPO into bulk cooking oil and packaged cooking oil. The method used is spectrophotometry. This research was conducted to test the content of β-carotenes in each sample during the processing. The difference between bulk cooking oil and packaged cooking oil depend on the raw material, processing time, and supporting material. The stages of the processing of bulk cooking oil and packaging consist of bleaching, deodorizing, and fractionation. β-carotenes levels in bulk CPO was found to be between 432.1156-434.9257 ppm, and packaging CPO ranged between 490.0259-491.9635 ppm. After fractionation,  it is obtained in bulk RBD Olein 5.4714-6.8757 ppm and packaged RBD olein 15.3098-16.8184 ppm. Thus, reduced content of β-carotenes during the processing of bulk and packaged cooking oil its about 98.5558% and 96.7456%.